C.S. Lewis and the church : essays in honour of Walter Hooper - Wolfe, Judith (Judith E.); Wolfe, B. N. (Brendan N.) (T & T Clark, 2011)
C.S. Lewis, himself a layperson in the Church of England, has exercised an unprecedentedly wide influence on the faithful of Anglican, Roman Catholic, Evangelical and other churches, all of whom tend naturally to claim him as ''one of their own''. One of the reasons for this diverse appropriation is the elusiveness of the church in the sense both of his own denomination and of the wider subject of ecclesiology in Lewis'' writings. The essays contained in this volume critically examine the place, character and role of the Church in Lewis'' life. The result is a detailed and scintillatin.